Age, Sex, and Valve Phenotype Differences in Fibro‐Calcific Remodeling of Calcified Aortic Valve - Martine Voisine; Maxime Hervault; Mylène Shen; Anne‐Julie Boilard; Benoît Filion; Mickael Rosa; Yohan Bossé; Patrick Mathieu; Nancy Côté; Marie‐Annick Clavel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background In calcific aortic valve disease on tricuspid aortic valves (TAVs), men have higher aortic valve calcification and less fibrosis than women. However, little is known in bicuspid aortic valves (BAV). We thus aimed to investigate the impact of age, sex, and valve phenotype (TAVs versus BAVs) on fibro‐calcific remodeling in calcific aortic valve disease. Methods and Results We included 2 cohorts: 411 patients who underwent multidetector computed tomography (37% women) for aortic valve calcification density assessment and 138 explanted aortic valves (histological cohort; 50% women). The cohorts were divided in younger (<60 years old) or older patients with BAV (≥60 years old), and TAV patients. In each group, women and men were matched. Women presented less aortic valve calcification density than men in each group of the multidetector computed tomography cohort (all P≤0.01). Moreover, in women, younger patients with BAV had the lowest aortic valve calcification density (both P=0.02). In multivariate analysis, aortic valve calcification density correlated with age (β estimate±standard error: 6.5±1.8; P=0.0004) and male sex (109.2±18.4; P<0.0001), and there was a trend with TAVs (41.5±23.0; P=0.07). Women presented a higher collagen content than men (77.8±10.8 versus 69.9±12.9%; P<0.001) in the entire cohort. In women, younger patients with BAV had denser connective tissue than TAV and older patients with BAV (both P≤0.05), while no difference was observed between men. Conclusions In calcific aortic valve disease, women had less calcification and more fibrotic remodeling than men, regardless of the phenotype of the valve or age of the patient. Moreover, younger women with BAVs had less valve calcification. Thus, mineralization/fibrosis of the aortic valve is likely to have sex/age‐specific mechanisms and be influenced by the valve morphology.